KLEBSIELLA PNEUMONIAE RESISTANT TO THIRD GENERATION CEPHALOSPORINS IN A HOSPITAL IN VENEZUELA: SPREAD OF ESBLPRODUCING ST70 AND ST1261 CLONES - Gonzalez, Ana Carolina; Nieves, Beatriz (European Scientific Journal, ESJ, 2014)
Objectives. To characterize K. pneumoniae isolates presenting decreased susceptibility to third generation cephalosporins, and isolated in two high risk units of the University of the Andes Hospital (HULA). Methods. We studied all the K. pneumoniae strains non-susceptible to third generation cephalosporins isolated from patients and the environment in the Neonatal High Risk Unit (NHRU) and Adult Intensive Care Unit (AICU) of the HULA in Merida, Venezuela, from February to March 2007, and from June to November 2009. Antibiotic susceptibility was tested by the diskdiffusion method and by the E-test method. Detection of blaÎ²LEE and blaAmpC genes was carried out by PCR and sequencing. The genetic relationship between the isolates was established by pulsed field gel Electrophoresis (PFGE) and Multilocus Sequence Typing (MLST). Results. In total 39 isolates non-susceptible to third generation cephalosporins were identified, 30 of them from the NHRU and 9 from the AICU; 20 isolates (51,28%) produced CTX-M-15, 8 (20,51 %) CTX-M-2, 8 (20,51%) SHV-12, 2 (5,12%) SHV-1 overproduction and 1 (2.56%) EBC. By PFGE, ten clusters were found. By MLST, the two more prevalent PFGE clusters belonged to ST70, (here reported for the first time in Venezuela), and ST126. Conclusions. Its to seem to be the first time, the dissemination of the ST70 clone producing CTX-M-15 in different risk units of LAUH is being described in Venezuela; also this is the first worldwide description the ST1261 clone producing CTX-M-2 and SHV-2.